Boosting the Energy Density of Aqueous Batteries via Facile Grotthuss Proton Transport. Issue 8 (21st December 2020) - Zhao, Qinghe; Song, Aoye; Zhao, Wenguang; Qin, Runzhi; Ding, Shouxiang; Chen, Xin; Song, Yongli; Yang, Luyi; Lin, Hai; Li, Shunning; Pan, Feng
Abstract: The recent developments in rechargeable aqueous batteries have witnessed a burgeoning interest in the mechanism of proton transport in the cathode materials. Herein, for the first time, we report the Grotthuss proton transport mechanism in α‐MnO2 which features wide [2×2] tunnels. Exemplified by the substitution doping of Ni (≈5 at.%) in α‐MnO2 that increases the energy density of the electrode by ≈25 %, we reveal a close link between the tetragonal‐orthorhombic (TO) distortion of the lattice and the diffusion kinetics of protons in the tunnels. Experimental and theoretical results verify that Ni dopants can exacerbate the TO distortion during discharge, thereby facilitating the hydrogen bond formation in bulk α‐MnO2 . The isolated direct hopping mode of proton transport is switched to a facile concerted mode, which involves the formation and concomitant cleavage of O−H bonds in a proton array, namely via Grotthuss proton transport mechanism. Our study provides important insight towards the understanding of proton transport in MnO2 and can serve as a model for the compositional design of cathode materials for rechargeable aqueous batteries. Abstract : This work demonstrates the promoting mechanism of Ni‐doping on the Grotthuss proton transport in [2×2] tunnels of α‐MnO2, attributing to a promoted TO distortion, which presents a general strategy for regulating the proton transport inside the tunnel structure of MnO2, as well as for designing high‐energy‐density cathode materials for future aqueous batteries.